Assessment of Environmental Exposure to Benzene: Traditional and New Biomarkers of Internal Dose - Lovreglio, Piero; D’Errico, Maria Nicolà; Fustinoni, Silvia; Drago, Ignazio; Barbieri, Anna; Sabatini, Laura; Carrieri, Mariella; Apostoli, Pietro; Soleo, Leonardo (IntechOpen, 2011)
None